2012
DOI: 10.1021/la303410w
|View full text |Cite
|
Sign up to set email alerts
|

Self-Generated Diffusioosmotic Flows from Calcium Carbonate Micropumps

Abstract: Calcium carbonate particles, ubiquitous in nature and found extensively in geological formations, behave as micropumps in an unsaturated aqueous solution. The mechanism causing this pumping is diffusioosmosis, which drives flows along charged surfaces. Our calcium carbonate microparticles, roughly ∼10 μm in size, self-generate ionic gradients as they dissolve in water to produce Ca(2+), HCO(3)(-), and OH(-) ions that migrate into the bulk. Because of the different diffusion coefficients of these ions, spontane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
111
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 99 publications
(116 citation statements)
references
References 40 publications
3
111
0
2
Order By: Relevance
“…Due to the diffusioosmotic effect, concentration gradients around dissolving salt particles (7,8) can drive the radial motion of tracer particles at speeds of ∼10 μm/s, which is similar in order of magnitude to the flows observed from enzyme pumps (2). Notably, the motion of a particle due to solute concentration gradients near a wall is a combination of the diffusioosmotic fluid flow u DO along the fixed wall and diffusiophoretic motion of the particle relative to the fluid flow, v DP , both of which are proportional to the quantity ∇C=C, where C is the solute concentration (5,7). Near an impermeable Significance Surface-bound enzymes act as pumps in the presence of their specific substrates or promoters, thereby combining sensing and fluidic pumping into a single self-powered microdevice.…”
Section: Resultsmentioning
confidence: 99%
“…Due to the diffusioosmotic effect, concentration gradients around dissolving salt particles (7,8) can drive the radial motion of tracer particles at speeds of ∼10 μm/s, which is similar in order of magnitude to the flows observed from enzyme pumps (2). Notably, the motion of a particle due to solute concentration gradients near a wall is a combination of the diffusioosmotic fluid flow u DO along the fixed wall and diffusiophoretic motion of the particle relative to the fluid flow, v DP , both of which are proportional to the quantity ∇C=C, where C is the solute concentration (5,7). Near an impermeable Significance Surface-bound enzymes act as pumps in the presence of their specific substrates or promoters, thereby combining sensing and fluidic pumping into a single self-powered microdevice.…”
Section: Resultsmentioning
confidence: 99%
“…Prieve (36) and coworkers noted an analogy with chemically reacting systems, e.g., as steel dissolution drives the diffusiophoretically accelerated deposition of latex particles. More recently, McDermott et al (65) showed that calcium carbonate particles dissolving in unsaturated aqueous solutions act as diffusioosmotic micropumps, driving flows along neighboring surfaces. Zheng and Pollack (66) reported long-range exclusion near hydrogel boundaries, and Florea et al (67) revealed ion exchange reactions to form a colloidal exclusion zone near membrane surfaces.…”
Section: Discussionmentioning
confidence: 99%
“…16,70 The practical side of this field will continue to develop as new collective phenomena are discovered and their mechanisms are better understood. Self-propelled autonomous motors make their own decisions based on the local environment.…”
Section: Accounts Of Chemical Researchmentioning
confidence: 99%